Alyceclover - Summer Annual Legume - J. Vendramini; A.R. Blount; J. Dubeux Jr. (EDIS)
Alyceclover [Alysicarpus vaginalis (L.) DC.] is a late-growing summer annual legume native to the tropics in Asia. This warm-season legume grows erect with spreading branches and may reach a height of 60" if not harvested. Although an annual, it can reestablish each year by natural reseeding if the crop is allowed to make seed in the fall. This may be difficult to accomplish since the crop is usually cut for hay or grazed closely, which eliminates seed production. Only seed of common alyceclover is available for planting. Common alyceclover has been grown in Florida for many years for either pasture or hay. Document first published April, 2000.-